2016
DOI: 10.48044/jauf.2016.033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Xylem Discoloration in Ash Trees Associated with Macroinjections of a Systemic Insecticide

Abstract: Emerald ash borer (EAB) (Agrilus planipennis), first identified near Detroit, Michigan, U.S., in 2002, has killed millions of ash trees (Fraxinus spp.) in 28 states and two Canadian provinces to date. Trunk injections of insecticide products containing emamectin benzoate (EB) (e.g., TREE-ageR) are often used to protect ash trees in landscapes from EAB, but wounds and potential injury resulting from injections are a concern. Researchers examined 507 injection sites on 61 trees and recorded evidence of secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Methods for freezing or drying partially processed splints that can be rehydrated also warrant consideration. Ongoing discussions among basketmakers include potentially using alternative materials to sustain traditional basketry practices such as Manchurian ash ( Fraxinus mandshurica ), an Asian species related to black ash but more resistant to EAB infestation (Tanis and McCullough 2016). Members of several Tribal Nations have participated in national or local efforts to collect and store seed from black ash populations to conserve genetic diversity prior to EAB invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Methods for freezing or drying partially processed splints that can be rehydrated also warrant consideration. Ongoing discussions among basketmakers include potentially using alternative materials to sustain traditional basketry practices such as Manchurian ash ( Fraxinus mandshurica ), an Asian species related to black ash but more resistant to EAB infestation (Tanis and McCullough 2016). Members of several Tribal Nations have participated in national or local efforts to collect and store seed from black ash populations to conserve genetic diversity prior to EAB invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The OTC formulation had a pH of 1.8 and the IMI formulation had a pH of 4.6, corresponding to more damage and discoloration caused by the former than the latter. However, the discoloration may also be, at least in part, associated with the color of the formulation (Tanis and McCullough 2016). Research on how the concentration and/or formulation of a specific crop protection material affects wound healing and compartmentalization as well as longer-term impact on tree health is necessary before using it on a larger scale.…”
Section: Discussionmentioning
confidence: 99%
“…Bark cracking was observed in this study and was included as a part of overall wounding. Tanis and McCollough [24] observed 5% of green ash and white ash (Fraxinus americana L.) trees developed bark cracking in their field study in central Michigan, MI USA. Aćimović et al [14] found vertical bark cracking occurred the first season with every system they studied.…”
Section: Implications Of Findingsmentioning
confidence: 99%
“…However, bark cracking or a canker may result from the wound associated with drilling and other factors as a part of tree injection. In two short-term studies with ash trees, after two years less than 5% of trees showed external bark cracking [23,24].…”
Section: Introductionmentioning
confidence: 99%